2021
DOI: 10.1371/journal.pone.0252922
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing clinical symptoms and treatment of patients with traffic accident injuries: A retrospective chart review with a questionnaire survey

Abstract: This study analyzed factors influencing clinical symptoms and treatment of patients with traffic accident injuries. It used a retrospective chart review and questionnaire survey obtained from 560 patients (266 men and 294 women). It also conducted follow-up observations of progress after car insurance settlements and investigated the usefulness of and patient satisfaction with integrative Korean medicine treatment for traffic accident injuries. Retrospective data of patients admitted for traffic accident injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Furthermore, a previous study reported that the TA-related settlement status and treatment completion status are associated with clinical symptoms after a TA. [ 30 ] This study lasted 12 weeks, including follow-up, to monitor clinical progress related to LBP, as well as the treatment completion status, accident settlement status, and return to work. However, no differences were observed between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a previous study reported that the TA-related settlement status and treatment completion status are associated with clinical symptoms after a TA. [ 30 ] This study lasted 12 weeks, including follow-up, to monitor clinical progress related to LBP, as well as the treatment completion status, accident settlement status, and return to work. However, no differences were observed between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to many researchers, after upper limb injuries in road traffic accidents, there is a noticeable decrease in quality of life during the initial acute phase, usually within 1-2 weeks after the injury, with gradual improvement over the first year of recovery [15][16][17]. Previous studies have highlighted the disabling nature of upper limb and chest injuries.…”
Section: E Discussionmentioning
confidence: 99%
“…[7] Furthermore, patients frequently exaggerate their symptoms for financial rewards from insurance companies. [8] Owing to these characteristics, clinicians often do not actively conduct…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Furthermore, patients frequently exaggerate their symptoms for financial rewards from insurance companies. [ 8 ] Owing to these characteristics, clinicians often do not actively conduct examinations to determine the anatomical origin of patients pain and overlook the diagnosis of obvious damage to body structures. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%